Antiamnesic potentials of ethyl acetate fraction of methanolic extract of Ayurvedic drug Desmodium triquetrum in mice: Desmodium triquetrum improves memory - JOSHI, HANUMANTHACHAR; CS, Charan; Abdo Alkanad, Majed (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Alzheimer’s disease is a neurodegenerative disorder associated with a decline in cognitive abilities. Dementia is one of the aged related mental problems and a characteristic symptom of Alzheimer’s disease. Nootropic agents like piracetam and cholinesterase inhibitors like Donepezil® are used in situations where there is organic disorder in learning abilities, but the resulting side-effects associated with these agents have limited their utility. Desmodium triquetrum is widely used in Indian traditional systems of medicines and also as a folk remedy for nervous debility. The present work was undertaken to assess the potential of D. triquetrum as a nootropic and anti-cholinesterase agent in mice. Exteroceptive behavioral models such as Elevated plus maze and Morris water maze were employed to assess short term and long term memory in mice. To delineate the possible mechanism through which D. triquetrum elicits the anti-amnesic effects, its influence on central cholinergic activity was studied by estimating the whole brain acetylcholinesterase activity. Pretreatment of ethyl acetate fraction of Methanolic extract of roots of D. triquetrum (50 and 100 mg/kg, p.o.) for 8 successive days, ameliorated the amnesic effect of scopolamine (0.4 mg/kg) and aging induced memory deficits in mice. D. triquetrum (100 mg/kg, p.o) significantly decreased transfer latencies of young mice and aged mice, decreased escape latency, TSTQ and exhibited significant anti-acetyl cholinesterase effects, when compared to piracetam, scopolamine and control groups of mice. D. triquetrum might prove to be a useful memory restorative agent in the treatment of dementia seen in the elderly. The underlying mechanism of its action may be attributed to its antioxidant, anti-inflammatory and acetyl cholinesterase inhibition property.